Like a Caged Bird: The Coping Strategies of Economically Empowered Women Who Are Victims of Intimate Partner Violence in Bangladesh - Akhter, Rifat (Journal of interpersonal violence, 2022)
This article identifies coping strategies used by economically empowered Bangladeshi women who are victims of intimate partner violence. Interviews were conducted with 19 employed women who experience abuse at the hands of their husbands and with eight community leaders. A ?Cultural Biography? approach was used to determine respondents? understanding of cultural phenomena and to gain life histories from victims in order to explore coping strategies in response to the harm experienced. Findings indicate that even though these women have access to financial resources due to their employment, many of them cope with the abuse by continuing to live in the home with the abuser because of the stigma surrounding divorce and the lack of laws that would grant them guardianship of the children or access to their property. Others live with family or friends in order to avoid the harassment experienced by divorcees. The few who sought more formal help from community leaders (4 of the 19) experienced pressure to remain in the marriage and, thus, the cycle of abuse continued. Community leaders supported the perceptions of the respondents emphasizing how cultural expectations for women?s role in Bangladesh limit her ability to leave an abusive home, even if she is employed. As presented by Welby?s patriarchal theory, we see that public patriarchy (oppression through norms, laws, and other social forces) supports private patriarchy (where men individually dominate their intimate partner), even for those women who are economically empowered.